Using PEDATI Model to Design Online Learning with Project Based Learning Approach in the Human Performance Technology Course - Lasamahu, Beatriks; Siregar, Eveline; Sukardjo, Moch (Journal of Education Research and Evaluation, 2021)
Online learning is a form of learning that can answer the times, technological advances and knowledge of learning development in universities. This study uses the R&D method in designing online learning. The online learning design is carried out on human performance technology courses using the PEDATI model combined with a project-based learning approach. The PEDATI model itself has several design steps starting from formulating online learning, mapping material, determining asynchronous or synchronous and designing the selected learning path. Asynchronous learning at PEDATI which consists of, deepening, applying and evaluating with a project-based learning approach that has six steps. The results of the research resulted in an online learning design which consisted of formulating learning outcomes, mapping materials, making asynchronous learning flows combined with project-based learning syntax.